Contraceptive non‐use and emergency contraceptive use at first sexual intercourse among nearly 12 000 Scandinavian women. (11th February 2017) - Guleria, Sonia; Juul, Kirsten E.; Munk, Christian; Hansen, Bo T.; Arnheim‐Dahlström, Lisen; Liaw, Kai‐Li; Nygård, Mari; Kjær, Susanne K.
Abstract: Introduction: The aim of this study was to describe recent patterns of contraceptive use at first sexual intercourse and to examine whether selected factors are associated with non‐use and emergency contraceptive pill use at first sexual intercourse, among 18‐ to 26‐year‐old women from Denmark, Norway and Sweden. Material and methods: This was a population‐based, questionnaire study of randomly chosen 18‐ to 26‐year‐old Scandinavian women. The prevalence of contraception methods used at first sexual intercourse was calculated. Factors associated with contraceptive non‐use and emergency contraceptive pill use at first sexual intercourse were determined using log binomial models. Results: The prevalence of contraceptive non‐use and emergency contraceptive pill use was lowest in Denmark (9.6 and 2.1%, respectively) compared with Norway (14.1 and 4.4%) and Sweden (16.6 and 4.5%). The risk of contraceptive non‐use increased in women who had first sexual intercourse at or before 14 years of age (13–14 years: prevalence ratio 1.40; 95% confidence interval 1.24–1.58). The risk of both non‐use and emergency contraceptive pill use increased when the partner at first sexual intercourse was 20 years or older, and with increasing age difference between the partner and the woman at her first sexual intercourse. Smoking initiation prior to first sexual intercourse increased risk of contraceptive non‐use (prevalence ratio 1.70; 95% confidence interval 1.50–1.92), and alcohol initiation prior to first sexual intercourse increased risk of emergency contraceptive pill use at first sexual intercourse (prevalence ratio 1.95; 95% confidence interval 1.49–2.54). Conclusions: Contraceptive non‐use at first sexual intercourse was strongly associated with early age at first sexual intercourse. Emergency contraceptive pill and contraceptive non‐use at first sexual intercourse were both strongly associated with increasing partner age and an increasing difference in age between the woman and her partner. Hence, young women should be educated to negotiate contraceptive use with their partners.